Sexuality and religion in transition : A longitudinal study of Croatian college students and sexual risks, 1998-2008 - Baćak, Valerio (Array, 2009)
Personal importance and political influence of religion increased substantially during the war-affected democratic transition in Croatia. Young people were particularly vulnerable in this process in regard to sexual behavior. Their sexual socialization was surrounded with mixed messages. On the one hand, Church promoted sexual abstinence as the only appropriate way toward sexual health ; while on the other hand, media were increasingly portraying images of sexual permissiveness. This paper examines one part of Croatian youth sexuality in transition: the impact of religiosity on sexual risk taking among young people using data from a longitudinal study conducted in 1998, 2003, and 2008 on probability samples of the University of Zagreb freshmen students. In particular, we looked at three hypotheses exploring both the risk-reducing role of religiosity, and the role it possibly has on risk-amplification. First, we hypothesized that religiosity is associated with lesser knowledge of human sexuality and more negative attitudes toward condom use ; second, that religiosity delays sexual debut ; and third, that religiosity decreases the odds of condom use. Students who scored high in religiosity had less favorable attitudes towards condoms and were less sexually literate than those who scored low in religiosity. In addition, religiosity was associated with a slight but significant postponement of sexual debut for both women and men. Two mechanisms are proposed as potential explanations for the somewhat surprising lack of significant association between religiosity and condom use. The first is the specific nature of religious identification among young people in Croatia. As recent studies suggested, religiosity is more often a confirmation of young people's national identity than a matter of faith and moral guidance. The second mechanism emphasizes the influence of sexual permissiveness discourse, promoted in popular media, on young people's framing and understanding of sexuality. Finally, considering that the observed increase in the proportion of sexually active students during the period between 1998 and 2008 was not matched by a parallel increase in consistent condom use, the introduction of a comprehensive school-based sexuality education seems essential for addressing this heightened vulnerability of young Croats to sexually transmitted infections.